2019
DOI: 10.3892/mmr.2019.9865
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression of genes involved in brain energy metabolism as adaptive responses in rats exposed to chronic variable stress; changes in cortical level of glucogenic and neuroactive amino acids

Abstract: Brain metabolism is closely associated with neuronal activity and enables the accurate synthesis and function of neurotransmitters. Although previous studies have demonstrated that chronic stress is associated with the overproduction of reactive oxygen species (ROS), which leads to oxidative stress and the disruption of glucose metabolism, the molecular mechanisms and cerebral gluconeogenesis in depression have not yet been completely elucidated. In order to examine this subject, the present study evaluated ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 55 publications
(88 reference statements)
0
5
0
Order By: Relevance
“…Human ASD, for example, exhibits increased synaptic density that can be reflected in increased synaptic relative to neuronal markers (31). In addition, increased oxidative stress in brain is characteristic of both ASD and ADHD in patients (32,33), and can be reflected by down-regulation of oxidative metabolic proteins such as GAPDH (34). Moreover, overexpression of transcriptional regulatory proteins such as eIF4E are sufficient to promote verified ASD-like behaviors in mice (35,36).…”
Section: Cd103-deficient Mice Exhibit Disorder-specific Brain Proteinmentioning
confidence: 99%
“…Human ASD, for example, exhibits increased synaptic density that can be reflected in increased synaptic relative to neuronal markers (31). In addition, increased oxidative stress in brain is characteristic of both ASD and ADHD in patients (32,33), and can be reflected by down-regulation of oxidative metabolic proteins such as GAPDH (34). Moreover, overexpression of transcriptional regulatory proteins such as eIF4E are sufficient to promote verified ASD-like behaviors in mice (35,36).…”
Section: Cd103-deficient Mice Exhibit Disorder-specific Brain Proteinmentioning
confidence: 99%
“…2 Stress can disrupt energy homeostasis by altering major metabolic processes such as hormone signaling and glucose uptake, 3 as well as alter gene expression related to glucose metabolism and reduce glucogenic and neuroactive amino acids. 4 Other evidence has shown that stress 5 increases consumption of fat-derived ketone bodies in the brain that varies across regions. 5 However, these studies focused on stressed-induced alterations of brain metabolism in the context of the general effects of stress on metabolic processes, and the subjects in these studies were passive recipients of stressful manipulations.…”
Section: Introductionmentioning
confidence: 99%
“…The frontal brain and hippocampus of depressed mice showed greater glucose/glycogen, and glucose transporter (GLUT1–GLUT3) levels than healthy animals due to the intensity of glucose uptake during depression [ 15 ]. A previous study examined the expression of glycolysis and glycogen-related genes in the hippocampus of depressed rats, and the results showed that the mRNA level of Slc2a3 (encoding GLUT3) increased [ 16 ]. According to certain hypotheses, the risk of developing mental, metabolic, and cardiovascular disorders is elevated by prolonged stimulation of the hypothalamic-pituitary-adrenal (HPA) axis.…”
Section: Introductionmentioning
confidence: 99%